Volume 3: 21st International Conference on Advanced Vehicle Technologies; 16th International Conference on Design Education 2019
DOI: 10.1115/detc2019-98402
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Energy Harvesting and Hydraulically Interconnected Suspension: Modeling and Validations

Abstract: This paper introduces a new form of energy-harvesting suspension that is integrated in a hydraulically interconnected suspension (HIS) system. The combined energy-harvesting and hydraulic interconnection features provide improved energy efficiency and vehicle dynamics performance. A half car model and a full car model are developed to validate the effectiveness of this design. Different dynamic input scenarios are used for model simulation, which includes single-wheel sinusoidal input, two-wheel sinusoidal inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The triboelectric effect has received enormous interest for its effective power generation function and was first proposed by Prof. Zhonglin Wang in 2012 as triboelectric nanogenerators (TENGs) [4]. Subsequently, many absorbing devices have been presented and studied, including TENGs with intense output power density, entirely newly designed structures for ocean energy harvesting, ultra-thin devices for wearable biophysiological sensing, and integration in diverse engineering applications [35][36][37][38][39][40][41][42][43]. Due to the synergistic effect of triboelectrification and electrostatic induction, TENG will generate the output signals continuously according to the external stimulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triboelectric effect has received enormous interest for its effective power generation function and was first proposed by Prof. Zhonglin Wang in 2012 as triboelectric nanogenerators (TENGs) [4]. Subsequently, many absorbing devices have been presented and studied, including TENGs with intense output power density, entirely newly designed structures for ocean energy harvesting, ultra-thin devices for wearable biophysiological sensing, and integration in diverse engineering applications [35][36][37][38][39][40][41][42][43]. Due to the synergistic effect of triboelectrification and electrostatic induction, TENG will generate the output signals continuously according to the external stimulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, linear narrow-band generators cannot adapt to variable environmental vibrations at any time and cannot provide a stable output. Therefore, Shahruz et al [37] proposed an array piezoelectric broadband generator. The different natural frequencies of the array cantilever beams increase the bandwidth of the generator.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [29] proposed a hydraulic energy-harvesting shock absorber prototype. An energy-harvesting suspension integrated in a hydraulically interconnected suspension system was introduced by Chen et al [30], which can generate up to 421 W at 4 Hz frequency and 40 mm displacement. Guntur et al [31] designed a hydro-magneto-electric regenerative shock absorber, and the maximum generated output power was 14 W at periodical input 1.5 Hz frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 37 ] integrated the energy harvesting shock absorbers into the hydraulic interconnected suspension system and indicated that the system performed better than the traditional suspension in terms of rolling dynamics and could harvest 421 W energy at 4 Hz and 40 mm (peak) excitation. Guo et al [ 38 ] proposed a hydraulic interconnected suspension system based on hydraulic electromagnetic shock absorbers, which only adopted one set of hydraulic motor-generator system and greatly reduced the cost while improving the energy recovery efficiency.…”
Section: Introductionmentioning
confidence: 99%